Smash, Forehand, Table Tennis The Effect of Arm Muscle Power Training and Hand Eye Coordination on the Accuracy of Table Tennis Smash Forehand on Athletes in the PTM Sukun Kudus Club - Prabowo, Frengki Setyo; Rustiadi, Tri; Priyono, Bambang (Journal of Physical Education and Sports, 2021)
The purpose of this study was to analyze the effect of arm muscle power exercise and hand eye coordination on the accuracy of table tennis forehand smash on athletes at PTM Sukun Kudus club. This type of research is quantitative research with experimental methods. The population used were all table tennis players at the PTM Sukun Kudus club, totaling 24 athletes. 8 male athletes and 16 female athletes at regional and national levels with a total sample of 24 athletes. The data analysis technique used is Two Way Anova. The results of the study stated that there was a significant effect between the dumbbell hight swing arm muscle power training method and push up exercises on the accuracy of the forehand smash on table tennis athletes at the PTM Sukun Kudus club. There is a significant effect between right and left hand eye coordination on the accuracy of the forehand smash on table tennis athletes at the PTM Sukun Kudus club.